2023
DOI: 10.1007/s40122-023-00565-3
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Modulation and Its Implications on Neuropathic Pain: A Comprehensive Literature Review

Alberto Corriero,
Mariateresa Giglio,
Francesco Inchingolo
et al.

Abstract: Neuropathic pain (NP) is a chronic pain disorder arising from somatosensory nervous system impairment. Extensive evidence supports the notion that the gut microbiota (GM) is crucial in maintaining human health by performing vital tasks. At the same time, its disruption has been linked to the emergence and advancement of an expanding range of disorders, including NP, in which GM could play a role in its pathophysiology. The crosstalk between the nervous system and GM happens through immune mediators, metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…GM may be pivotal in the pathogenesis of OA itself and the perception of the pain that accompanies this condition [ 68 ].…”
Section: The Gut–joint Axis: How Dysbiosis Leads To Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…GM may be pivotal in the pathogenesis of OA itself and the perception of the pain that accompanies this condition [ 68 ].…”
Section: The Gut–joint Axis: How Dysbiosis Leads To Osteoarthritismentioning
confidence: 99%
“…It was shown that removing both superior cervical ganglia substantially impacted the composition of GM, suggesting that the sympathetic pathway plays a function in controlling GM [ 89 ]. Similarly, the vagus nerve and the enteric nervous system are critical links between GM and the peripheral nervous system [ 68 ]. Specifically, the vagus nerve has a dual purpose: it establishes a direct link between the gastrointestinal system and the brain, functioning as a conduit for all the GM mediators.…”
Section: The Gut–joint Axis: How Dysbiosis Leads To Osteoarthritismentioning
confidence: 99%
“…Trillions of microorganisms cohabit with cells inside the human organism, influencing health and quality of life [4][5][6][7]. The most important density of microorganisms is reached in the gut, where it is called the intestinal microbiome [8]. The importance of intestinal microbiome can be correlated with human development, metabolism, and behavior [9][10][11].…”
Section: Introductionmentioning
confidence: 99%